Critical Hermeneutics of Patriarchal Exegesis: Muhammad Arkoun’s Applied Islamology Approach in Interpreting Gender Verses - Masykuroh, Siti (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract This study examines the patriarchal construction in classical interpretations of QS. al-Nisāʾ [4]:34 and QS. al-Baqarah [2]:228, and deconstructs them through Muhammad Arkoun’s critical hermeneutics (Applied Islamology). The main issue addressed is the dominance of classical interpretations by al-Ṭabarī, Ibn Kathīr, and al-Qurṭubī, which emerged from patriarchal social structures and a closed epistemology, thereby marginalizing alternative perspectives. The aim of this study is to offer a more ethical and humanistic reinterpretation by emphasizing gender justice. The research employs a qualitative method with critical discourse analysis, integrating exegesis, anthropology, sociology, and linguistics. The novelty of this study lies in the application of Arkoun’s Apply Islamology through the concept of epistemic break and openness to the unsaid, in order to dismantle the hegemony of patriarchal interpretations. Its contribution is to open up a space for reinterpretation of Islamic teachings that is more contextual, responsive to contemporary social dynamics, and supportive of the principle of gender equality. Keywords: Applied Islamology; Critical hermeneutics; Gender justice; Muhammad Arkoun; Patriarchal exegesis.